366 An Audit of Electronic Discharge Summaries and the Impact of Dedicated Teaching and Training in an Emergency Surgical Unit. (28th February 2022) - Clements, J.; Kakos, C.; Clements, B.
Abstract: Introduction: Electronic discharge summary forms a vital part of a patient's journey. As established in GAIN Guidelines 2011 'Clear and complete documentation in a patient's health record is directly linked to the quality of the care they receive'. By improving the quality of E-Discharge summaries this will help to improve patient outcomes. Method: In the Emergency surgical unit [EMSU] there are over 3500 completed consultant episodes per annum. We audited the quality of E-Discharges using 33 separate parameters included in the Trust's dedicated discharge proforma. An E-Discharge summary was considered acceptable if >90% of the information was recorded accurately. Discharge failure rate was audited in a randomised sample of 20 discharges in November 2019 and one year later in November 2020 following implementation of specific training and teaching at induction on E-Discharge compilation. Results: In November 2019 the discharge failure rate was 60%. Common failings were in general omission of data, lack of follow-up planning and inaccurate pharmaceutical arrangements. In November 2020, following dedicated teaching at induction, failure rate was 15%. Where accurate recording of demographic information and pertinent inpatient detail improved, shortcomings remained in inadequate recording of follow-up care and ongoing involvement of the primary healthcare team. Conclusions: E-Discharge recording is sub-standard. It is often the remit of the least experienced member of the medical team, as is the case in our unit. We have shown that dedicated teaching and training in this area can improve the quality of discharge summaries.